1998
DOI: 10.1007/bf02768756
|View full text |Cite
|
Sign up to set email alerts
|

Does aggregation substance ofEnterococcus faecalis contribute to development of endocarditis?

Abstract: Aggregation substance (AS) of Enterococcus faecalis which is encoded by so-called sex pheromone plasmids enables the bacteria to bind to in vitro-cultured pig kidney tubular cells. It is reported that the presence of AS is not of pivotal importance for the ability of E. faecalis to cause infective endocarditis (EN). The lines of evidence for this are twofold: 1) sex pheromone plasmids and, therefore, the gene for AS were not present more often in epidemiologically unrelated strains of E. faecalis isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Another study with the rabbit model of enterococcal endocarditis also documented that the presence of the AS in combination with the expression of the enterococcal binding substance caused high mortality (26). In other animal models (experimental endocarditis and experimental endophthalmitis), the AS had no influence on the outcome of the infections (3,14). These experimental models, however, do not reflect a situation where the enterococci have to adhere to intestinal epithelia and translocate through the mucosa.…”
mentioning
confidence: 99%
“…Another study with the rabbit model of enterococcal endocarditis also documented that the presence of the AS in combination with the expression of the enterococcal binding substance caused high mortality (26). In other animal models (experimental endocarditis and experimental endophthalmitis), the AS had no influence on the outcome of the infections (3,14). These experimental models, however, do not reflect a situation where the enterococci have to adhere to intestinal epithelia and translocate through the mucosa.…”
mentioning
confidence: 99%
“…Results from our laboratory with E. faecalis containing variants of pCF10 (45) also supported these findings in that AS both increased the size of vegetations and increased mortality. However, Berti et al (5) used a rat endocarditis model with pAD1 derivatives and concluded that AS had no significant influence on the virulence of the organism. Inducible expression of AS alone in a heterologous host (Lactococcus lactis) has provided evidence for increased binding to fibrin as well as elevated cell surface hydrophobicity (20).…”
mentioning
confidence: 99%
“…However, in a rabbit model of endocarditis, a disease in which vegetations of platelets and fibrin resulting from bacterial infection are associated with inflammation of the heart valves and lining, aggregation substance from both pAD1 and pCF10 caused an increase in the size of cardiac vegetations (88, 90, 129). No effect of aggregation substance on vegetation size was observed in a rat endocarditis model (138), suggesting that the effects of aggregation substance on pathogenesis may be species or model-specific. The role of aggregation substance in an infection may be to promote the formation of a quorum of cells in a localized microenvironment through clumping, which could affect the expression of factors now known to be quorum regulated, such as the cytolysin (139).…”
Section: Virulence Plasmids In Enterococcus Faecalismentioning
confidence: 97%